Conservation Analysis and Colorimetric Characterization of Betalain Extracts from the Peel of Red Beetroot, Golden Beetroot, and Prickly Pear Applied to Cottage Cheese - Elizabeth López-Solórzano; Claudia Muro; Yolanda Alvarado Perez; Andrea Y. Guadarrama-Lezama; Elsa Gutiérrez-Cortez; Juan Manuel Urrieta (Foods)
The maintenance of betalains and the color of extracts from the peel of red beetroot (RBAC), golden beetroot (YBAC), and purple prickly pear (PBAC) were evaluated, describing the capacity of their use as natural pigments and in the formulation of attractive and functional foods. Betalain extracts were prepared as juices from frozen and dehydrated peel, adding organic acids and concentrating for water reduction. Extracts were evaluated and applied on cottage cheese, measuring the capacity of betalains retention and pigmentation, during 10 days of storage of closed and opened products. Extracts of RBAC showed the highest betacyanin concentration, followed by YBAC with betaxanthins and PBAC with less betacyanin content. The pH stability for the extracts was pH4–7; RBAC and PBAC were stables at <90 °C, whereas YBAC exposed >125 °C. Extracts were constant during 10 days under oxygen and light exposure; however, YBAC exhibited low resistance in this environment. With cottage cheese, extracts exposed no changes in betalains and color on closed products (10 days of storage at 4 °C). In opened products, PBAC maintained the maximum betalains and color at 90%, PBAC at 75%, and YBAC at 60%. The obtained data contributed to use of agro-industrial residues, betalain extraction and conservation, and their potential use in food coloration and stabilization.